Optical Field Localization in the Three-Dimensional Percolating System with Gaussian Distribution Disorder - Erika Martinez Sanchez; Gennadiy Burlak; Gustavo Medina Angel; Ricardo Magallanes Rivera (International Journal of Optics)
We study the optical field generated by nanoemitters incorporated in a three-dimensional percolation system, where the probability p of pore occupation is well above the threshold value p≫0.318. In the proposed system, the pores are randomly distributed in a cubic grid, and the radii of the pores are adjusted by the Gaussian distribution. Maxwell’s equations in conjunction with the four-level laser equations are applied to the proposed random medium. The finite-difference time-domain algorithm (FDTD) is used to obtain the field pattern and optical modes within the system. We show that the number of optical modes increases with the size of the system, thus contributing to cylindrical symmetric geometries that guide the light beam in a particular direction. Confinement in one direction could be used as a random laser waveguide, with some characteristics similar to those of conventional lasers.